2024
DOI: 10.3390/cancers16071273
|View full text |Cite
|
Sign up to set email alerts
|

RUVBL1 in Clear-Cell Renal Cell Carcinoma: Unraveling Prognostic Significance and Correlation with HIF1A

Justyna Durślewicz,
Aleksandra Maria Wybierała,
Sara Szczepanek
et al.

Abstract: This study investigates the roles of RUVBL1 and HIF1A in ccRCC development and explores their clinical significance as prognostic biomarkers. mRNA and protein expressions were analyzed using TCGA data and an institutional tissue cohort, respectively. Correlations with clinicopathological parameters and patient outcomes were assessed. TCGA data revealed significantly elevated RUVBL1 mRNA expression in ccRCC tissues, associated with advanced histological grade, T stage, lymph node metastasis, and clinical stage.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Prior studies have indicated a dual role of TGF-β in breast cancer, initially exerting tumor-suppressive effects in early stages and transitioning to pro-tumorigenic effects in later stages 62 . As our survival analysis relied on transcriptomic data from TCGA database, the discordance between mRNA and protein expression patterns and biological mechanisms was elucidated 63 . Consequently, potential disparities may exist between the regulatory effects of DHODH expression at the RNA level, and its effects on ccRCC development and patient survival at the protein level.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have indicated a dual role of TGF-β in breast cancer, initially exerting tumor-suppressive effects in early stages and transitioning to pro-tumorigenic effects in later stages 62 . As our survival analysis relied on transcriptomic data from TCGA database, the discordance between mRNA and protein expression patterns and biological mechanisms was elucidated 63 . Consequently, potential disparities may exist between the regulatory effects of DHODH expression at the RNA level, and its effects on ccRCC development and patient survival at the protein level.…”
Section: Discussionmentioning
confidence: 99%